The Effect of River Rafting Experiences on Tourists’ Stress Levels in Pangalengan, Bandung Regency - Keneisha Kayla Qintharie; Dally Nur Arif; Gilang Pratama Putra (Eduvest - Journal of Universal Studies, 2026)
The development of adventure tourism encourages an increase in tourist interest in activities that not only provide entertainment, but also have an impact on psychological conditions. One of these activities is rafting in Pangalengan which has increased visits every year. This research aims to analyze the influence of the experience of rafting tourism activities on the stress level of tourists. The method used is a quantitative approach with a causal associative design. The research sample of 366 respondents was determined using the purposive sampling technique. Data was collected through questionnaires and analyzed using simple linear regression. The results of the study showed that the experience of rafting tourism had a significant effect on the stress level of tourists, as evidenced by a significance value of 0.000 < 0.05 and a determination coefficient value of 0.529. This shows that travel experiences contribute 52.9% to the variation in tourist stress levels. Thus, the better the experience that tourists feel, the stress level tends to decrease. This study confirms that adventure-based tourism activities can be an effective alternative in reducing stress and improving the psychological well-being of tourists.